2016
DOI: 10.4257/oeco.2016.2001.04
|View full text |Cite
|
Sign up to set email alerts
|

POPULATION BIOLOGY OF THE MELON CACTUS Melocactus violaceus subsp. violaceus (CACTACEAE) ON A BRAZILIAN SANDY COASTAL PLAIN

Abstract: There is a notable lack of ecological information about South American cacti species and the existing information isn't evenly distributed among life forms and geographic regions. Here, the population structure of a globose cactus species (Melocactus violaceus) on a Brazilian restinga was described and the patterns presented were compared with those reported to other Melocactus species. Cacti density observed on the study area was lower than that reported to other species of the genus. No association between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
1
0
1
9
Order By: Relevance
“…Consistent with previous observations, I found a significant non-dependence of growth forms on the cactus abundance (i.e., all size classes) (Figueira et al 1994;Figueiredo 2016). Furthermore, M.v.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous observations, I found a significant non-dependence of growth forms on the cactus abundance (i.e., all size classes) (Figueira et al 1994;Figueiredo 2016). Furthermore, M.v.…”
Section: Discussionsupporting
confidence: 91%
“…Differing from the findings of Figueiredo (2016), where over half of the population was in pre-reproductive and reproductive stages, totalizing 56.5% of the population, only 3% of the individuals registered in our study were in reproductive stage, being closer to the population structure observed by García-González et al (2016), where 28.7% of the Melocactus nagyi Z.…”
Section: Discussioncontrasting
confidence: 75%
“…Melocactus violaceus não possui estudos moleculares sobre a riqueza genética de suas populações. Mas Figueiredo (2016) trouxe informações sobre a estrutura da população da espécie em uma restinga do Rio de Janeiro, que são relevantes para entender a estrutura e dinâmica da população encontrada em Guadalupe. A primeira observação é que a população de M. violaceus no Rio de Janeiro em geral apresenta uma densidade muito menor do que a verificada para outras espécies do gênero em outros estudos.…”
Section: Cryptanthus Zonatusunclassified
“…Um fato observado durante nossa análise da população da praia de Guadalupe é que os indivíduos além de esparsos formavam uma população muito pequena. Figueiredo (2016) também constatou que a população da restinga de Jurubatiba possui uma predominância de indivíduos jovens. Durante nosso estudo foram constatados menos que dez indivíduos apresentando o cefálio, indicativo da maturidade reprodutiva nas espécies do gênero Melocactus (Taylor, 1991).…”
Section: Cryptanthus Zonatusunclassified
See 1 more Smart Citation